Upgrading Our Electronics and Downgrading Their Environment: How E-Waste Recycling Has Made China Our Backyard Dumping Ground - Stephanie Tso (Washington University Journal of Law & Policy, 2013)
The city of Guiyu, China was a sleepy farming community not long ago before the city became the largest electronic waste (“e- waste”) repository on earth. Since 1995, Guiyu has been completely transformed. Aptly nicknamed an electronic graveyard, Guiyu has become infamous for its role as the epicenter for crude electronic recycling. Electronics, mostly from the United States, are frequently discarded to be recycled. However, instead of ending up in local recycling facilities in the United States, they are sold and shipped off to China where they are crudely broken, melted, burned, and stripped down to copper, tin, gold, and plastic bits to be resold in a second- hand market desperate for such raw materials. This is the “dirty little secret of the electronic age.” Electronic recycling in Guiyu is generally set up as a family endeavor. Even children help by using small hands to sort out “tiny specks of wrong colored plastic chips.” In this small village, electronic components spill into backyards and onto streets. Rivers run black with toxins and ash, and the air is filled with acrid smoke from the open burning of circuit boards and computer wires. Workers with little to no protective clothing brush toner from discarded printers with their bare hands. It is easy to dismiss this distressing depiction as an isolated and remote matter to those living in the United States: however, it is important to remember that the source of the e-waste that litters this small village’s landscape comes from the homes of those living in the United States, thousands of miles away. Even though the problem of e-waste plagues only those far away, in this globalized world nothing is ever too far removed, and that which afflicts the backyard afflicts the home. This Note posits that the creation of e-waste in the United States has risen at an increasingly unsustainable rate. Continuing to dump e- waste in the backyard of China cannot be a long-term solution to this problem. This Note seeks to evaluate the current legal regulations governing the issue as well as seek new solutions to the problem. Part I traces the historical, technical, and geographical journey of e-waste from the United States to China. Part II examines the current legislation that governs e-waste. Part III analyzes the effects of the current legislation, as well as the deficiencies of such legislation. More attention should be paid by the legislative branch to deal with the mounting problem of e-waste and a more efficient and responsible system should be put in place to prevent rampant e-waste creation and exportation.
Keywords: electronic recycling; China; e-waste; legislation